Common Fixed Point Theorem on Cone Banach Space - Varghese, P.G.; Dersanambika, K.S. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The aim of this manuscript is to discuss some fixed point results for self mappings satisfying certain contractive conditions on Cone Banach space.